Can integrated interventions create the conditions that support caregiving for better child growth? - Menon, Purnima; Frongillo, Edward A. (Elsevier, 2018)
Children born to healthy mothers who live in homes with piped water and improved sanitation, are fed adequate diets, and have appropriate health care have better growth outcomes. Yet intervention trials to test the effects of integrated delivery of specific interventions that address elements of these determinants—such as the Articles by Stephen Luby and colleagues and Clair Null and colleagues reported in this issue of The Lancet Global Health—have come up short.